The discovery of TNF-alpha: a historical perspective - Kustrimovic, Natasa; Gallo, Daniela; De Lerma Barbaro , Andrea; Piantanida, Eliana; Mortara, Lorenzo; Tanda, Maria Laura (Medicina Historica, 2023)
Tumor necrosis factor (TNF), also known as TNF-alpha (TNF-α), is a pleiotropic pro-inflammatory cytokine that exerts multiple biologic effects. The research journey into the role of TNF has been a roller- coaster ride filled with ups and downs and it is still ongoing. At its discovery, huge expectations were laid upon this cytokine going so far that the cloning of human TNF, which had been achieved and published in 1984, was examined in the general press around the globe, and its therapeutic potential in cancer treatment was welcomed as the opening of a new era in cancer treatment. Nevertheless, the first clinical studies did not yield the expected results and it seemed for a moment that the glory of TNF was ending. But the discovery of the pro-inflammatory effect of TNF changed the course of the research journey of this cytokine. TNF is a highly pleiotropic cytokine and accordingly, it plays a pivotal role in many physiological functions, and is involved in a wide variety of pathological conditions. TNF has become a major target in chronic inflammatory diseases, and its neutralization have delivered the first insights into the development of a novel category of pharmaceuticals, the “biological drugs”.